Treatment of metastatic uveal melanoma with adoptive transfer of tumour-infiltrating lymphocytes: a single-centre, two-stage, single-arm, phase 2 study. Issue 6 (June 2017) - Chandran, Smita S; Somerville, Robert P T; Yang, James C; Sherry, Richard M; Klebanoff, Christopher A; Goff, Stephanie L; Wunderlich, John R; Danforth, David N; Zlott, Daniel; Paria, Biman C; Sabesan, Arvind C; Srivastava, Abhishek K; et al.
Summary: Background: Uveal melanoma is a rare tumour with no established treatments once metastases develop. Although a variety of immune-based therapies have shown efficacy in metastatic cutaneous melanoma, their use in ocular variants has been disappointing. Recently, adoptive T-cell therapy has shown salvage responses in multiple refractory solid tumours. Thus, we sought to determine if adoptive transfer of autologous tumour-infiltrating lymphocytes (TILs) could mediate regression of metastatic uveal melanoma. Methods: In this ongoing single-centre, two-stage, phase 2, single-arm trial, patients (aged ≥16 years) with histologically confirmed metastatic ocular melanoma were enrolled. Key eligibility criteria were an Eastern Cooperative Oncology Group performance status of 0 or 1, progressive metastatic disease, and adequate haematological, renal, and hepatic function. Metastasectomies were done to procure tumour tissue to generate autologous TIL cultures, which then underwent large scale ex-vivo expansion. Patients were treated with lymphodepleting conditioning chemotherapy (intravenous cyclophosphamide [60 mg/kg] daily for 2 days followed by fludarabine [25 mg/m 2 ] daily for 5 days, followed by a single intravenous infusion of autologous TILs and high-dose interleukin-2 [720 000 IU/kg] every 8 h). The primary endpoint was objective tumour response in evaluable patients per protocol using Response to Evaluation Criteria in Solid Tumors, version 1.0. An interim analysis of this trial is reported here. The trial is registered atClinicalTrials.gov, numberNCT01814046 . Findings: From the completed first stage and ongoing expansion stage of this trial, a total of 21 consecutive patients with metastatic uveal melanoma were enrolled between June 7, 2013, and Sept 9, 2016, and received TIL therapy. Seven (35%, 95% CI 16–59) of 20 evaluable patients had objective tumour regression. Among the responders, six patients achieved a partial response, two of which are ongoing and have not reached maximum response. One patient achieved complete response of numerous hepatic metastases, currently ongoing at 21 months post therapy. Three of the responders were refractory to previous immune checkpoint blockade. Common grade 3 or worse toxic effects were related to the lymphodepleting chemotherapy regimen and included lymphopenia, neutropenia, and thrombocytopenia (21 [100%] patients for each toxicity); anaemia (14 [67%] patients); and infection (six [29%] patients). There was one treatment-related death secondary to sepsis-induced multiorgan failure. Interpretation: To our knowledge, this is the first report describing adoptive transfer of autologous TILs to mediate objective tumour regression in patients with metastatic uveal melanoma. These initial results challenge the belief that metastatic uveal melanoma is immunotherapy resistant and support the further investigation of immune-based therapies for this cancer. Refinement of this T-cell therapy is crucial to improve the frequency of clinical responses and the general applicability of this treatment modality. Funding: Intramural Research Program of the National Institutes of Health, National Cancer Institute, Center for Cancer Research.